Falling upward eaudiobook A spirituality for the two halves of life. - Rohr, Richard (Tantor Media, 2024)
In the revised and updated edition of Falling Upward , Richard Rohr seeks to help listeners come to terms with the two halves of life. In this book, Rohr teaches us that we can't understand the meaning of "up" until we have fallen "down." More importantly, Rohr describes what "up" can look like in the second half of life. Most of us tend to think of the second half of life in chronological terms, but this book proposes a different paradigm. Spiritual maturity is found "when we begin to pay attention and seek integrity" through a shift from our "outer task" to the "inner task." Falling Upward is an invitation to living the gospel and a call to ongoing transformation. ● Gain a spiritual perspective on the "the common sequencing, staging, and direction of life's arc" and learn how to bring forth your gifts in the second half of life ● Grapple with difficult feelings, fears, and emotions associated with "great love and great suffering" ● Learn how we "grow spiritually much more by doing it wrong than by doing it right" ● Understand why so many of us resist falling into the second half of life.